Diffuse interstitial lung disease--evaluation with high-resolution computed tomography - Herman, M; Kolek, V (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1993)
We evaluated patterns of normal and abnormal lung parenchyma on standard 8-mm computed tomography (CT) scans, and 1-mm or 2-mm high-resolution CT (HRCT) scans in 22 subjects. There were five control subjects with no lung symptoms, and 17 patients with proved diagnosis of diffuse interstitial diseases consisting of sarcoidosis (n = 7), bronchioloalveolar carcinoma (n = 3), extrinsic allergic alveolitis (n = 2), asbestosis (n = 2), scleroderma (n = 2), and drug toxicity (n = 1). CT and HRCT scans were evaluated for specific parenchymal features particularly the distribution in secondary pulmonary lobule; conditions of pleura, mediastinum, and thoracic wall were appreciated. CT and HRCT findings were described in individual disease. We believe that CT and HRCT are useful investigations in patients with suspected or known diffuse interstitial lung diseases. At present time CT, and particularly HRCT seem to be the best available method to image the lung parenchyma.
Keywords: referenční hodnoty; počítačová rentgenová tomografie; nádory plic; Lung Neoplasms; Humans; lidé středního věku; Female; Aged; dospělí; Lung; intersticiální plicní nemoci; senioři; lidé; plíce; Adult; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Aged, 80 and over; Reference Values; senioři nad 80 let; Lung Diseases, Interstitial; mužské pohlaví